2009
DOI: 10.1038/sj.bjc.6605053
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and quality of care of cancer pain management. Results from the Cancer Pain Outcome Research Study Group

Abstract: Most patients with advanced or metastatic cancer experience pain and despite several guidelines, undertreatment is well documented. A multicenter, open-label, prospective, non-randomised study was launched in Italy in 2006 to evaluate the epidemiology, patterns and quality of pain care of cancer patients. To assess the adequacy of analgesic care, we used a standardised measure, the pain management index (PMI), that compares the most potent analgesic prescribed for a patient with the reported level of the worst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 26 publications
6
112
2
8
Order By: Relevance
“…In a prospective study performed by Apolone et al (2009) at 110 sites (specific oncology, pain, palliative and care centers) in 1802 outpatients and in-patients with advanced stage and metastatic solid tumor, even though sufficient analgesic supplementation was provided to the patients, pain palliation has been ensured only in 25.3% of patients according to PMI (Apolone et al, 2009. It has reported that 11% of patients with moderate-severe intensity of pain received no treatment for pain (Breivik et al, 2009).…”
Section: Prevalencementioning
confidence: 99%
“…In a prospective study performed by Apolone et al (2009) at 110 sites (specific oncology, pain, palliative and care centers) in 1802 outpatients and in-patients with advanced stage and metastatic solid tumor, even though sufficient analgesic supplementation was provided to the patients, pain palliation has been ensured only in 25.3% of patients according to PMI (Apolone et al, 2009. It has reported that 11% of patients with moderate-severe intensity of pain received no treatment for pain (Breivik et al, 2009).…”
Section: Prevalencementioning
confidence: 99%
“…The results of their study mentioned the mildest pain of 1.9; worst pain 6.7; and a mean of 4.1 degrees. In general, the results of this model of pain management research can be an answer solution from some literature that mentions the inadequate management of cancer pain (Apolone et al, 2009Foley, 2011 or has not been handled thoroughly (Desen&Japaries, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The authors planned to carry out a systematic review based on an electronic search of 5 databases, including the contact of the original authors of the primary studies for clarification, or to obtain missing information or individual data. Finally, on the basis of the results of this review and according to the preliminary results of a prospective outcome research study carried out in Italy on 1800 cancer patients with pain, 50 a multicenter RCT to compare the efficacy of 4 strong opioids on cancer pain (buprenorphine, morphine, fentanyl, and oxycodone) will be launched at the end of this year, involving about 80 centers and 1000 patients.…”
Section: Dovepressmentioning
confidence: 99%